(untitled) (Communications in Computational Physics, 2010)
In this paper we present the modelling of elastic intra-species electron-electron and inter-species electron-ion scattering in a plasma on the basis of the Fokker-Planck collision operator. Taking into account the equivalence of this operator with a stochastic differential equation, we propose a Particle-in-Cell based approach for the numerical solution of the Fokker-Planck collision term. As we will see, the introduced numerical concept allows the simulation of the collisional relaxation process in a fully self-consistent fashion.